Electrical characterization of Pt/SrBi2Ta2O9/Pt capacitors fabricated by the pulsed laser ablated deposition technique - Lee, JK; Jung, HJ; Auciello, O; Kingon, AI (A V S AMER INST PHYSICS, 1996)
Pulsed laser ablation deposition was used to synthesize polycrystalline SrBi2Ta2O9 layered ferroelectric thin films on the platinized silicon substrate. The surface roughness of the deposited film was an average of 4 nm. The titanium element was diffused to the SrBi2Ta2O9 layer through the platinum layer. P-E hysteresis loop for the Pt/SrBi2Ta2O9/Pt/Ti capacitor was well saturated and symmetric (P-r = 3 mu C/cm(2), E(c) = 25 kV/cm). (C) 1996 American Vacuum Society.